EPCT-04. RESULTS OF A PHASE 1 STUDY OF THE ONCOLYTIC ADENOVIRUS DNX-2401 WITH RADIOTHERAPY FOR NEWLY DIAGNOSED DIFFUSE INTRINSIC PONTINE GLIOMA (DIPG). (1st June 2021) - Garcia-Moure, Marc; Pérez-Larraya, Jaime Gállego; Patiño, Ana; Gonzalez-Huarriz, Marisol; Jones, Chris; MacKay, Alan; Van der Lugt, Jasper; Hulleman, Esther; de Andrea, Carlos; Astigarraga, Itziar; García-Ariza, Miguel; Lopez-Ibor, Blanca; et al.
Abstract: Background: A Phase 1, single center study is ongoing to evaluate the conditionally replicative oncolytic adenovirus, DNX-2401 (tasadenoturev), followed by radiotherapy (RT) in pediatric patients with newly diagnosed diffuse intrinsic pontine glioma (DIPG). Methods: Patients 1–18 years with newly diagnosed DIPG with no prior treatment, Lansky/Karnofsky performance score ≥ 70, and adequate organ function were enrolled. A tumor biopsy was performed followed by a single intratumoral injection of 1e10-5e10 virus particles (vp) DNX-2401. Conventional radiotherapy was initiated within 1 month of DNX-2401 administration. Results: Enrolled subjects (n=12) had a median age of 9 (range 3–18) and performance scores of 90–100 (n=4; 33%) or 70–80 (n=8; 67%). As part of a dose escalation design, subjects were treated with 1e10 vp (n=4) or 5e10 vp DNX-2401 (n=8), which was then followed by standard RT in 11 of 12 subjects (92%). No dose-limiting toxicities were observed and the treatment regimen was well-tolerated. Adverse events (AEs) have been primarily mild to moderate and consistent with underlying disease. The most commonly reported AEs (≥ 5 subjects), regardless of study drug relationship, include headache, asthenia, vomiting, anemia, leukocytosis, and fever. Two SAEs have been reported including grade 3 lymphopenia and grade 3 abdominal pain. Tumor reductions have been observed and efficacy evaluations are ongoing. As of 09Dec2020, 12-month survival (OS-12) was 71% and 4 of 12 patients had survived > 20 months. Four subjects continue to be followed for survival. Correlative analysis of tumor biopsy and peripheral samples is ongoing. Conclusions: DNX-2401 followed by RT can be safely administered to pediatric subjects with newly diagnosed DIPG; clinical activity and preliminary survival are encouraging.